The Dentin Microbiome: A Metatranscriptomic Evaluation of Caries-Associated Bacteria - Simone G. de Oliveira; Rodrigo Jardim; Nelson Kotowski; Alberto M. R. Dávila; Hélio R. Sampaio-Filho; Karina G. S. Ruiz; Flávio H. B. Aguiar (Biomedicines)
Background/Objectives: Dental caries remains a prevalent chronic disease globally, driven by complex interactions between the host, diet, and microbial communities. This study employs a metatranscriptomic RNA-Seq analysis to explore the functional dynamics of the dentin microbiome in both healthy and carious teeth. By examining the transcriptional activity of bacterial communities, we aimed to identify key microbial species and molecular functions associated with caries progression. Methods: Samples from six patients (three healthy and three decayed teeth) were analyzed using the Illumina NovaSeq 2000 platform, with data processed through the SAMSA2 pipeline for taxonomic and functional annotation. Results: The differential expression analysis revealed significant upregulation of Streptococcus and Lactobacillus species, including S. mutans, S. sobrinus, and L. salivarius, in carious samples, highlighting their roles in acid production and carbohydrate metabolism. Additionally, Mycobacterium species, known for their biofilm-forming capabilities and acid tolerance, were upregulated in decayed teeth. The Gene Ontology (GO) enrichment analysis identified unique molecular functions and biological processes in carious teeth, such as carbohydrate metabolism, oxidative stress response, and bacterial cell wall biogenesis, which are critical for microbial survival in acidic environments. In contrast, healthy teeth exhibited functions related to homeostasis and nutrient acquisition, reflecting a balanced microbial community. Conclusions: The study underscores the polymicrobial nature of dental caries, with multiple bacterial species contributing to disease progression through diverse metabolic and stress-response mechanisms. These findings provide deeper insights into the ecological shifts within the oral microbiome during caries development, emphasizing the importance of a functional metatranscriptomic analysis in understanding the pathogenesis of dental caries.